2012
DOI: 10.1101/gr.138032.112
|View full text |Cite
|
Sign up to set email alerts
|

Correlated alterations in genome organization, histone methylation, and DNA–lamin A/C interactions in Hutchinson-Gilford progeria syndrome

Abstract: Hutchinson-Gilford progeria syndrome (HGPS) is a premature aging disease that is frequently caused by a de novo point mutation at position 1824 in LMNA. This mutation activates a cryptic splice donor site in exon 11, and leads to an in-frame deletion within the prelamin A mRNA and the production of a dominant-negative lamin A protein, known as progerin. Here we show that primary HGPS skin fibroblasts experience genome-wide correlated alterations in patterns of H3K27me3 deposition, DNA-lamin A/C associations, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
272
3
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 291 publications
(311 citation statements)
references
References 41 publications
29
272
3
1
Order By: Relevance
“…6A,B). Consistent with previous studies (Ly et al ., 2000; Park et al ., 2001; Csoka et al ., 2004; McCord et al ., 2013), there are more than 20% differentially expressed genes (up/down: 7.79%/14.18%) in HGPS cells vs. normal fibroblasts (Fig. 6A‐1).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…6A,B). Consistent with previous studies (Ly et al ., 2000; Park et al ., 2001; Csoka et al ., 2004; McCord et al ., 2013), there are more than 20% differentially expressed genes (up/down: 7.79%/14.18%) in HGPS cells vs. normal fibroblasts (Fig. 6A‐1).…”
Section: Resultsmentioning
confidence: 97%
“…Previous studies reported that the anchorage of progerin to the nuclear membrane caused a loss of perinuclear heterochromatin in HGPS cells (Goldman et al ., 2004; McCord et al ., 2013). Using TEM technology, we examined this progerin‐directed nuclear phenotype in mock‐ and MB‐treated HGPS cells and observed an obvious restoration of perinuclear heterochromatin organization after MB treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A decrease in repression‐associated H3K27me3 (and an increased activity of the H3K27me3 demethylase KDM6A/UTX) is a key feature of the global chromatin reconfiguration occurring not only in somatic cells during the normal aging process but also in prematurely aging cells in HGPS and WS (Scaffidi & Misteli, 2005; Shah et al., 2013; Shumaker et al., 2006). In addition, landmark observations in Caenorhabditis elegans have linked gain of H3K27me3 (and loss of the H3K27me3 demethylase UTX‐1) to extended longevity, strongly suggesting that preserving high levels of H3K27me3 by inhibiting KDM6/UTX may be critical for maintaining youthfulness (Jin et al., 2011; Maures et al., 2011; McCord et al., 2013; Shah et al., 2013). Despite conflicting data from different model systems, there is a trend for increases in activating histone marks (e.g., H3K4m2/3, H3K36me3) and decreases in repressive histone marks (e.g., H3K9m2/3, H3K27me3) indicative of a more actively transcribed genome, which is consistent with a well‐recognized open chromatin conformation in aging cells and organisms that culminates in the so‐called heterochromatin loss model of aging (Pal & Tyler, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several reports have found progerin, and increasing levels of progerin, in normal cells over the course of normal aging (Scaffidi & Misteli, 2006; McClintock et al ., 2007; Cao et al ., 2007; Rodriguez et al ., 2009), which suggests a similar genetic mechanism in HGPS and normal aging. Moreover, genome‐scale expression profiling in cells from HGPS patients, as well as in physiological aging, has revealed widespread transcriptional misregulation in multiple mammalian tissues (Ly et al ., 2000; Csoka et al ., 2004; Zahn et al ., 2007; Scaffidi & Misteli, 2008; Cao et al ., 2011; McCord et al ., 2013). …”
Section: Introductionmentioning
confidence: 99%